2012
DOI: 10.1017/s003118201200039x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of avian haemosporidians in arid zones of northern Venezuela

Abstract: Arid zones of northern Venezuela are represented by isolated areas, important from an ornithological and ecological perspective due to the occurrence of restricted-range species of birds. We analysed the prevalence and molecular diversity of haemosporidian parasites of wild birds in this region by screening 527 individuals (11 families and 20 species) for parasite mitochondrial DNA. The overall prevalence of parasites was 41%, representing 17 mitochondrial lineages: 7 of Plasmodium and 10 of Haemoproteus. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 52 publications
6
18
0
1
Order By: Relevance
“…In addition, we found that the prevalence of Haemoproteus in birds was higher than that seen for Plasmodium . This finding is consistent with previous studies, which showed that Haemoproteus was generally more prevalent than Plasmodium [38], [40], [41]. This difference might be explained by the fact that Haemoproteus has lower pathogenicity in its host than Plasmodium [10], [42].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we found that the prevalence of Haemoproteus in birds was higher than that seen for Plasmodium . This finding is consistent with previous studies, which showed that Haemoproteus was generally more prevalent than Plasmodium [38], [40], [41]. This difference might be explained by the fact that Haemoproteus has lower pathogenicity in its host than Plasmodium [10], [42].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we found that Plasmodium prevalence was higher than Haemoproteus prevalence. Although this finding complies with the previous study performed in southeast Brazil, most of the studies in bird communities of South and North America show a higher prevalence of Haemoproteus [11,17,31,[34][35][36]. This contrary scenario presented by the malarial parasite community from southeast Brazil could be explained by differences of vector populations, Culicidae mosquitoes for Plasmodium and biting midges (Culicoides) and louse-flies (Psedolynchia, Microlynchia and Ornithomyia) for Haemoproteus [2], because the distribution of malaria vectors can be affected by vegetation type, rainfall patterns, mean temperatures, elevation, and geomorphology [37].…”
Section: Diversity and Distribution Of Parasite Lineagessupporting
confidence: 92%
“…In the present study, we performed the first molecular characterization of the malarial parasites in bird communities from southeast Brazil. The overall prevalence (35.3%) observed was similar to other community-level studies that used PCR screening approaches and were performed in tropical habitats of South America [16][17]26]. However, the observed prevalence was higher than that found in previous studies that adopted only blood smear screening approaches [27][28][29][30][31].…”
Section: Diversity and Distribution Of Parasite Lineagessupporting
confidence: 80%
See 1 more Smart Citation
“…We recorded lineage occurrence information using the 'Hosts and Sites' query in the MalAvi database to record the country where sampling was conducted and the academic reference for each lineage occurrence (Bensch et al 2009). To maximise the dataset, we included cyt-b lineages that were amplified from a different region of the parasite cyt-b gene (Fallon et al 2003, Belo et al 2012, Fecchio et al 2013, Svensson-Coelho et al 2013 .…”
Section: 1: Observed and Estimated Lineage Richnessmentioning
confidence: 99%